The prevalence and diagnostic classification of mixed features in patients with major depressive episodes: A multicenter study based on the DSM‐5 - Shim, In Hee; Lee, Jonghun; Kim, Moon‐Doo; Jung, Young‐Eun; Min, Kyung Joon; Kwon, Young‐Joon; Kim, Ji Sun; Lee, Kwanghun; Woo, Young Sup; Nam, Beomwoo; Seo, Jeong Seok; Lee, Jung Goo; et al. (International journal of methods in psychiatric research, 2019)
Objectives The purpose of this study was to evaluate the prevalence of mixed features using the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5) and to examine how patients with mixed states would be classified using the DSM‐5. Methods In total, 12 hospitals participated in this study, and data on the demographic characteristics and clinical diagnoses of patients treated between October 2013 and September 2016 were obtained. We reviewed the data for opposite‐polarity symptoms according to the DSM‐5 criteria and the research‐based diagnostic criteria. Results Of the 859 patients included in the final analysis, the prevalence of mixed features in patients with major depressive episodes based on the DSM‐5 remained low. Patients with major depressive disorder were more likely to be classified as experiencing anxious distress and/or a cluster‐B personality disorder in mixed state patients not diagnosed with DSM‐5 mixed features, whereas more mixed state patients with bipolar disorder were diagnosed with mixed features using the DSM‐5. Conclusions The prevalence of mixed features did not increase significantly when the DSM‐5 was used, and patients with mixed states were more likely to be classified as having anxious distress and/or a cluster‐B personality disorder in addition to mixed features.